The Representative Meaning of Longing in Mahmoud Darwish's "Ila Ummi" Poem Viewed from a Semantic Approach - Makrifah, Nurul; Intan Sari, Dewi (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
Poetry is one literary form that requires comprehension. Therefore, this study examines the lexical, grammatical, and referential meanings of the poems in Ila Ummi. By summarizing the data gathered, this study employs descriptive qualitative research methodology. The poem Ila Ummi by Mahmoud Darwish, which can be found in his poetry collection Aasyiq Min Filastiin, serves as the primary data source for this study. Books, journals, and other supporting materials make up the secondary data. The study's findings indicate that Ila Ummi's poetry has referential, grammatical, and lexical semantic meanings. Grammatical meaning is the meaning of a sentence that varies due to structural changes, as opposed to lexical meaning, which is the meaning stated in a dictionary or refers to the real meaning. Furthermore, this paper investigates the role of figurative language, metaphor, and symbolism in conveying the emotional depth of longing in "Ila Ummi." The poet's use of metaphors, such as the land as a mother, and symbols, like the olive tree, are explored to unveil the layers of meaning that these elements contribute to the overall semantic structure of the poem. This study contributes to the understanding of Mahmoud Darwish's work as a literary and cultural artifact that transcends individual sentiment and embodies the collective experience of longing for a homeland. By employing a semantic approach, the paper highlights the poem's ability to evoke many emotions and associations, making "Ila Ummi" a profound representation of longing that resonates with readers on both personal and universal levels.